Application of liquid nitrogen rapid cooling in preparation of nickel-manganese-based sodium ion battery positive electrode material

The cathode material of nickel-manganese-based sodium ion battery is rapidly cooled by liquid nitrogen rapid cooling technology, which solves the problem of poor material circulation stability and rate performance in traditional methods, and achieves the improvement of the material's high structural stability and electrochemical performance.

CN119674055APending Publication Date: 2025-03-21SICHUAN UNIVERSITY OF SCIENCE AND ENGINEERING
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411669875.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The traditional method of preparing the positive electrode material of nickel-manganese-based sodium ion battery has problems with poor material cycle stability and rate performance, and it is difficult to accurately control the microstructure of the material.

Method used

Using liquid nitrogen rapid cooling technology, in the process of preparing the positive electrode material of nickel-manganese-based sodium ion battery, the material is rapidly cooled to room temperature, significantly changing the microstructure and chemical state of the material, thereby improving its electrochemical performance.

Benefits of technology

Through the rapid cooling technology of liquid nitrogen, the structural stability and kinetic performance of the cathode material of nickel-manganese-based sodium ion battery is significantly improved, its cycle stability and rate performance is enhanced, production cycles are shortened and costs are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119674055A_ABST
    Figure CN119674055A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of chemical power sources, and particularly relates to application of liquid nitrogen rapid cooling in preparation of a nickel-manganese-based sodium ion battery positive electrode material. The sodium-ion battery positive electrode material is synthesized by taking Ni0. 25Mn0. 75 (OH) 2 as a precursor, adding a sodium source and adopting a high-temperature solid-phase method, and the material subjected to high-temperature calcination by liquid nitrogen is rapidly cooled during cooling, so that the local chemical environment of the sodium-ion battery positive electrode material is obviously changed, and the performance of the sodium-ion battery positive electrode material is improved. Therefore, the prepared nickel-manganese-based sodium-ion battery positive electrode material shows excellent electrochemical performance in a wide potential range of 2.0-4.3 V and still has high specific discharge capacity after 100 cycles, and meanwhile, the air stability of the material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of chemical power sources, and specifically relates to the application of rapid cooling of liquid nitrogen in the preparation of positive electrode materials for nickel-manganese-based sodium ion batteries. Background Art

[0002] With the growing demand for energy storage, sodium-ion batteries (SIBs) have attracted widespread attention due to their low cost, abundant resources and environmental friendliness, and are regarded as an effective alternative to lithium-ion batteries. In sodium-ion batteries, the performance of the cathode material directly affects the electrochemical performance of the battery, including energy density, cycle stability and rate performance. Nickel-manganese-based sodium-ion battery cathode materials have become a hot topic of research due to their high specific capacity and good structural stability.

[0003] However, traditional preparation methods often have some limitations, for example, the material's cycle stability and rate performance are not ideal, which is closely related to the microstructure and chemical state of the cathode material. Studies have shown that the synthesis and heat treatment process of the material, especially the cooling process, has a decisive influence on its final electrochemical performance.

[0004] In the traditional calcination process, natural cooling is usually conducive to the reinsertion of sodium ions, which helps to form a stable phase interface and thus improve the cyclic stability of the material. However, this cooling method often leads to a long preparation cycle of the material and it is difficult to accurately control the microstructure of the material. Summary of the invention

[0005] In order to solve at least one of the above problems, the present invention provides the use of liquid nitrogen rapid cooling in the preparation of nickel-manganese-based sodium ion battery positive electrode materials, which also includes a sodium ion battery positive electrode material and a preparation method thereof. In this solution, liquid nitrogen rapidly cools the material, effectively improving the structural stability and kinetic performance of the layered oxide positive electrode active material, so that the battery containing the sodium ion battery positive electrode material has a long cycle life.

[0006] In order to achieve the above invention object, the specific technical solution of the present invention is:

[0007] This application protects the application of rapid cooling of liquid nitrogen in enhancing the performance of nickel-manganese-based sodium-ion battery positive electrode materials.

[0008] Furthermore, in the above-mentioned application, the battery positive electrode material is a nickel-manganese-based sodium ion battery positive electrode material.

[0009] Furthermore, the above-mentioned application includes the following steps: first preparing a cathode material precursor; then rapidly cooling the cathode material precursor to room temperature using liquid nitrogen to obtain a nickel-manganese-based sodium ion battery cathode material. Preferably, the rapid cooling rate using liquid nitrogen is 70-90°C / min (specifically 70°C / min, 72°C / min, 74°C / min, 76°C / min, 78°C / min, 80°C / min, 82°C / min, 84°C / min, 86°C / min, 88°C / min, 90°C / min, etc.).

[0010] Furthermore, in the above-mentioned application, the enhanced performance of the nickel-manganese-based sodium-ion battery positive electrode material is to enhance the electrochemical performance of the nickel-manganese-based sodium-ion battery positive electrode material, including improving specific capacity and cycle stability.

[0011] As a preferred embodiment of the present application, the present application also provides a method for preparing a nickel-manganese-based sodium ion battery positive electrode material, which comprises the following steps:

[0012] S1: Use ball milling method to mix a certain proportion of Na salt and Ni 0.25 Mn 0.75 (OH) 2 The precursors are fully mixed to obtain a reaction mixture precursor;

[0013] S2: calcining the reaction mixture precursor of step S1 at 400-500° C. (specifically 400° C., 450° C., 500° C., etc.) for 5-7 h (specifically 5 h, 6 h, 7 h, etc.) to obtain a molten precursor;

[0014] S3: heating the molten precursor to 900-1000° C. (specifically 900° C., 950° C., 1000° C., etc.), calcining for 18-20 h (specifically 18 h, 19 h, 20 h, etc.) to obtain a calcined precursor of the positive electrode material;

[0015] S4: naturally cooling the cathode material precursor to 400°C-600°C and maintaining the temperature for 4-5 hours to obtain the cathode material precursor;

[0016] S5: Rapidly cool the cathode material precursor to room temperature using liquid nitrogen to obtain a manganese-based sodium ion battery cathode material.

[0017] Furthermore, in the method for preparing the positive electrode material of the nickel-manganese-based sodium ion battery, the Na salt and the Ni 0.25 Mn 0.75 (OH) 2 The molar ratio of the precursors is 0.54-0.72:1.

[0018] Furthermore, in the method for preparing the nickel-manganese-based sodium-ion battery positive electrode material, the Na salt is selected from the corresponding acetate or carbonate.

[0019] Furthermore, in the method for preparing the nickel-manganese-based sodium-ion battery positive electrode material, the cooling rate of the rapid cooling by liquid nitrogen is more than 10 times the natural cooling rate.

[0020] The present application also protects the nickel-manganese-based sodium ion battery positive electrode material prepared by any of the above methods or combinations of method steps.

[0021] Furthermore, the above-mentioned nickel-manganese-based sodium ion battery positive electrode material has a capacity retention rate of 80% after long cycles at a voltage of 2-4.3V.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] (i) The present invention can effectively improve the electrochemical properties of nickel-manganese-based sodium ion battery positive electrode materials prepared from commercial precursors through liquid nitrogen rapid cooling technology, while shortening the production cycle, reducing production costs, and improving the cycle stability and rate performance of the materials, and has significant industrial application potential.

[0024] (ii) The present invention uses liquid nitrogen rapid cooling technology to prepare nickel-manganese-based sodium-ion battery positive electrode materials, which achieves significant technical and economic advantages compared to traditional methods. This innovative method suppresses undesirable phase changes in the material by rapid cooling, thereby maintaining the microstructure of the material and enhancing the electrochemical properties, such as improving specific capacity and cycle stability. In addition, liquid nitrogen rapid cooling technology speeds up the heat treatment process of the material, significantly shortens the production cycle, and improves production efficiency. By changing the amount of liquid nitrogen added to accurately control the cooling rate at 70-90℃ / min, the crystal structure and surface properties of the material are optimized, further enhancing its electrochemical activity and stability.

[0025] (III) The present invention improves the safety of operation, uses liquid nitrogen, speeds up the production rate, and is more environmentally friendly. In addition, the material prepared by the liquid nitrogen rapid cooling technology exhibits excellent discharge specific capacity and cycle stability at high rates, making it more widely applicable and commercially viable in the application of positive electrode materials for sodium ion batteries.

[0026] (IV) The positive electrode material of the sodium ion battery is Ni 0.25 Mn 0.75 (OH) 2As a precursor, a sodium source is added, and a high-temperature solid-phase method is used for synthesis. When cooling, the material calcined at high temperature with liquid nitrogen is rapidly cooled, which significantly changes the local chemical environment of the positive electrode material of the sodium ion battery, so that the prepared nickel-manganese-based sodium ion battery positive electrode material exhibits excellent electrochemical performance in a wide potential range of 2.0-4.3V, and still has a high discharge specific capacity after 100 cycles, while improving the air stability of the material. Therefore, the present invention not only makes a breakthrough in technology, but also shows its comprehensive advantages at the economic and environmental levels. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The electron paramagnetic resonance spectra of the positive electrode materials obtained by natural cooling and liquid nitrogen cooling;

[0028] Figure 2 X-ray diffraction patterns of cathode materials obtained by different cooling methods and liquid nitrogen cooling;

[0029] Figure 3 The first cycle charge and discharge curves of the positive electrode materials obtained by different cooling methods and liquid nitrogen cooling at 0.1C;

[0030] Figure 4 The charge and discharge curves of the positive electrode material obtained by natural cooling and liquid nitrogen cooling at 0.5C for the 1st, 50th and 100th cycles;

[0031] Figure 5 The cyclic voltammetry curves of the positive electrode materials obtained by different cooling methods and liquid nitrogen cooling;

[0032] Figure 6 Electrochemical impedance spectra of the cathode materials obtained by different cooling methods and liquid nitrogen cooling;

[0033] Figure 7 The cycle curves of the positive electrode material obtained by different cooling methods and liquid nitrogen cooling;

[0034] Figure 8 The rate curves of the positive electrode materials obtained by different cooling methods and liquid nitrogen cooling. DETAILED DESCRIPTION

[0035] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with examples. It should be understood that the specific examples described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, it should be understood that after reading the content of the present invention, those skilled in the art can make various changes and modifications to the present invention, but these equivalent forms also fall within the scope defined by the claims attached to the application.

[0036] Embodiment 1:

[0037] This embodiment relates to the preparation of a positive electrode material for a sodium ion battery, and the specific operations are as follows:

[0038] S1. First, according to the predetermined molar ratio, weigh 5g of Ni 0.25 Mn 0.75 (OH) 2 Precursor and 1.67g sodium carbonate. The weighed materials are added to the ball mill, and 10mL of anhydrous ethanol is measured with a measuring cylinder and added thereto to achieve adequate mixing and uniform wetting.

[0039] S2, the ball mill is placed in a planetary ball mill, and the ball milling treatment is performed for 30 minutes at a speed of 600 rpm to ensure that the precursor and the Na salt are fully mixed and form a uniform precursor mixture. After the ball milling is completed, the mixture is taken out and placed in an oven at 120° C. for drying for 8 hours to remove moisture from the mixture, and a dry reaction mixture precursor is obtained.

[0040] S3, placing the dried precursor mixture into a muffle furnace, calcining at 400° C. for 7 hours to form a molten precursor, then raising the temperature to 1000° C. and continuing calcining for 18 hours to form a positive electrode material calcined precursor.

[0041] S4. After the high-temperature calcination is completed, the muffle furnace is closed, and the temperature in the furnace is allowed to naturally drop to 400° C. and maintained in this temperature range for 5 hours to complete the heat treatment of the positive electrode material precursor.

[0042] S5. The heat-treated positive electrode material precursor is taken out of the furnace, and quickly immersed in liquid nitrogen (-196°C, the same below) for rapid cooling, so that the material is cooled to room temperature at 70°C / min to obtain nickel-manganese-based sodium ion battery positive electrode material 1#.

[0043] Embodiment 2:

[0044] This embodiment relates to the preparation of a positive electrode material for a sodium ion battery, and the specific operations are as follows:

[0045] S1. First, according to the predetermined molar ratio, weigh 5g Ni 0.25 Mn 0.75 (OH) 2 Precursor and 1.86g sodium acetate. The weighed materials are added to the ball mill, and 15mL of anhydrous ethanol is measured with a measuring cylinder and added thereto to achieve adequate mixing and uniform wetting.

[0046] S2, the ball mill is placed in a planetary ball mill, and the ball milling treatment is performed for 40 minutes at a speed of 500 rpm to ensure that the precursor and the Na salt are fully mixed and form a uniform precursor mixture. After the ball milling is completed, the mixture is taken out and placed in a vacuum oven at 105° C. for drying for 12 hours to remove moisture from the mixture, and a dry reaction mixture precursor is obtained.

[0047] S3, placing the dried precursor mixture into a muffle furnace, and calcining it at 500° C. for 6 hours to form a molten precursor. Subsequently, the temperature is raised to 900° C., and calcining is continued for 20 hours to form a positive electrode material calcined precursor.

[0048] S4. After the high-temperature calcination is completed, the muffle furnace is closed, and the temperature in the furnace is allowed to naturally drop to 400° C. and maintained in this temperature range for 5 hours to complete the heat treatment of the positive electrode material precursor.

[0049] S5. Take out the heat-treated positive electrode material precursor from the furnace, quickly immerse it in liquid nitrogen for rapid cooling, and cool the material to room temperature at 80°C / min to obtain nickel-manganese-based sodium ion battery positive electrode material 2#.

[0050] Embodiment 3:

[0051] S1. First, according to the predetermined molar ratio, weigh 5g Ni 0.25 Mn 0.75 (OH) 2 Precursor and 2.07 g sodium carbonate (sodium salt in the example should be clear). The weighed materials are added into a ball mill, and 15 mL of anhydrous ethanol is measured with a measuring cylinder and added thereto to achieve adequate mixing and uniform wetting.

[0052] S2, the ball mill is placed in a planetary ball mill, and the ball milling treatment is performed for 30 minutes at a speed of 600 rpm to ensure that the precursor and the Na salt are fully mixed and form a uniform precursor mixture. After the ball milling is completed, the mixture is taken out and placed in a vacuum oven at 110° C. for drying for 10 hours to remove moisture from the mixture, and a dry reaction mixture precursor is obtained.

[0053] S3, placing the dried precursor mixture into a muffle furnace, and calcining at 450° C. for 6 hours to form a molten precursor. Subsequently, the temperature is raised to 1000° C., and calcining is continued for 18 hours to form a positive electrode material calcined precursor.

[0054] S4. After the high-temperature calcination is completed, the muffle furnace is closed, and the temperature in the furnace is allowed to naturally drop to 500° C. and maintained in this temperature range for 5 hours to complete the heat treatment of the positive electrode material precursor.

[0055] S5. Take out the heat-treated cathode material precursor from the furnace, quickly immerse it in liquid nitrogen for rapid cooling, and cool the material to room temperature at a rate of 85°C / min to obtain material 3#.

[0056] Embodiment 4:

[0057] S1. First, according to the predetermined molar ratio, weigh 5g Ni 0.25 Mn 0.75 (OH) 2 Precursor and 2.16g sodium acetate. The weighed materials are added into the ball mill, and 15mL of anhydrous ethanol is measured with a measuring cylinder and added thereto to achieve adequate mixing and uniform wetting.

[0058] S2, the ball mill is placed in a planetary ball mill, and the ball milling treatment is performed for 20 minutes at a speed of 1000 rpm to ensure that the precursor and the Na salt are fully mixed and form a uniform precursor mixture. After the ball milling is completed, the mixture is taken out and placed in a vacuum oven at 115° C. for drying for 9 hours to remove moisture from the mixture, and a dry reaction mixture precursor is obtained.

[0059] S3, placing the dried precursor mixture into a muffle furnace, and calcining it at 600° C. for 5 hours to form a molten precursor. Subsequently, the temperature is raised to 900° C., and calcining is continued for 19 hours to form a positive electrode material calcined precursor.

[0060] S4. After the high-temperature calcination is completed, the muffle furnace is closed, and the temperature in the furnace is allowed to naturally drop to 600° C. and maintained in this temperature range for 4 hours to complete the heat treatment of the positive electrode material precursor.

[0061] S5. Take out the heat-treated cathode material precursor from the furnace, quickly immerse it in liquid nitrogen for rapid cooling, and cool the material to room temperature at 70°C / min to obtain material 4#.

[0062] Comparative Example 1:

[0063] S1. First, according to the predetermined molar ratio, weigh 5g Ni 0.25 Mn 0.75 (OH) 2 Precursor and 2.07 g sodium carbonate (sodium salt in the example should be clear). The weighed materials are added into a ball mill, and 15 mL of anhydrous ethanol is measured with a measuring cylinder and added thereto to achieve adequate mixing and uniform wetting.

[0064] S2, the ball mill is placed in a planetary ball mill, and the ball milling treatment is performed for 30 minutes at a speed of 600 rpm to ensure that the precursor and the Na salt are fully mixed and form a uniform precursor mixture. After the ball milling is completed, the mixture is taken out and placed in a vacuum oven at 105° C. for drying for 12 hours to remove moisture from the mixture, and a dry reaction mixture precursor is obtained.

[0065] S3, placing the dried precursor mixture into a muffle furnace, calcining at 400° C. for 7 hours to form a molten precursor, then raising the temperature to 1000° C. and continuing calcining for 18 hours to form a positive electrode material calcined precursor.

[0066] S4. After the high-temperature calcination is completed, the muffle furnace is closed, and the temperature in the furnace is allowed to naturally drop to 400° C. and maintained in this temperature range for 5 hours to complete the heat treatment of the positive electrode material precursor.

[0067] S5. Take out the heat-treated cathode material precursor from the furnace, quickly put it into a glove box filled with argon gas, and allow the material to cool naturally to room temperature at a cooling rate of 5°C / min to obtain material 5#.

[0068] Comparative Example 2:

[0069] S1. First, according to the predetermined molar ratio, weigh 5g Ni 0.25 Mn 0.75 (OH) 2 Precursor and 2.07g sodium carbonate. The weighed materials are added to the ball mill, and 15mL of anhydrous ethanol is measured with a measuring cylinder and added thereto to achieve adequate mixing and uniform wetting.

[0070] S2, the ball mill is placed in a planetary ball mill, and the ball milling treatment is performed for 30 minutes at a speed of 600 rpm to ensure that the precursor and the Na salt are fully mixed and form a uniform precursor mixture. After the ball milling is completed, the mixture is taken out and placed in a vacuum oven at 105° C. for drying for 12 hours to remove moisture from the mixture, and a dry reaction mixture precursor is obtained.

[0071] S3, placing the dried precursor mixture into a muffle furnace, calcining at 400° C. for 7 hours to form a molten precursor, then raising the temperature to 1000° C. and continuing calcining for 18 hours to form a positive electrode material calcined precursor.

[0072] S4. After the high-temperature calcination is completed, the muffle furnace is closed, and the temperature in the furnace is allowed to naturally drop to 400° C. and maintained in this temperature range for 5 hours to complete the heat treatment of the positive electrode material precursor.

[0073] S5. Take the heat-treated cathode material precursor out of the furnace, and quickly put the material into a vacuum oven set at a constant temperature of 25°C to cool it down, so that the material is cooled to room temperature at a rate of 20°C / min, to obtain material 6#. Comparative Example 3:

[0074] S1. First, according to the predetermined molar ratio, weigh 5g Ni 0.25 Mn 0.75 (OH) 2 Precursor and 2.07g sodium carbonate. The weighed materials are added to the ball mill, and 15mL of anhydrous ethanol is measured with a measuring cylinder and added thereto to achieve adequate mixing and uniform wetting.

[0075] S2, the ball mill is placed in a planetary ball mill, and the ball milling treatment is performed for 30 minutes at a speed of 600 rpm to ensure that the precursor and the Na salt are fully mixed and form a uniform precursor mixture. After the ball milling is completed, the mixture is taken out and placed in a vacuum oven at 105° C. for drying for 12 hours to remove moisture from the mixture, and a dry reaction mixture precursor is obtained.

[0076] S3, placing the dried precursor mixture into a muffle furnace, calcining at 400° C. for 7 hours to form a molten precursor, then raising the temperature to 1000° C. and continuing calcining for 18 hours to form a positive electrode material calcined precursor.

[0077] S4. After the high-temperature calcination is completed, the muffle furnace is closed, and the temperature in the furnace is allowed to naturally drop to 400° C. and maintained in this temperature range for 5 hours to complete the heat treatment of the positive electrode material precursor.

[0078] S5. Take out the heat-treated cathode material precursor from the furnace, quickly transfer the material to a 5 mL beaker chilled in an ice bath and seal it, and cool the material to room temperature at 30°C / min to obtain material 7#.

[0079] The nickel-manganese-based sodium ion battery positive electrode materials obtained in Examples 1-4 and Comparative Examples 1-3 were subjected to conventional performance tests, and the specific results of the oxygen vacancy determination are shown in Figure 1-Figure 8 .

[0080] Depend on Figure 1 It can be seen that the material cooled by liquid nitrogen has fewer oxygen vacancies, indicating that its structural integrity is better.

[0081] Depend on Figure 2 It can be seen that the diffraction peak of the material cooled by liquid nitrogen has the highest degree of shift to low angles, indicating that its structural layer spacing is larger and has faster reaction kinetics.

[0082] Depend on Figure 3 , 4, 5, 7, and 8 show that the material that has been rapidly cooled by liquid nitrogen has a lower degree of structural change during the battery cycle and a higher structural stability.

[0083] Depend on Figure 6 It can be seen that the material that has been rapidly cooled by liquid nitrogen has a smaller internal resistance, which means that the transmission rate of electrons inside it is higher.

[0084] The above-mentioned embodiments only express the specific implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the protection scope of the present application. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the technical solution concept of the present application, and these all belong to the protection scope of the present application.

[0085] This background section is provided to generally present the context of the invention, and the work of the presently named inventors, the work to the extent described in this background section, and aspects of this section that did not constitute prior art at the time of application are neither explicitly nor implicitly admitted to be prior art to the present invention.

Claims

1. Application of rapid cooling of liquid nitrogen in enhancing the performance of battery positive electrode materials.

2. The use according to claim 1, characterized in that: The battery positive electrode material is a nickel-manganese-based sodium ion battery positive electrode material.

3. The use according to claim 1, characterized in that The following steps are involved: First, a positive electrode material precursor is prepared; then the positive electrode material precursor is rapidly cooled to room temperature using liquid nitrogen to obtain a nickel-manganese-based sodium ion battery positive electrode material.

4. The use according to any one of claims 1 to 3, characterized in that: The enhanced performance of the nickel-manganese-based sodium-ion battery positive electrode material is to enhance the electrochemical performance of the nickel-manganese-based sodium-ion battery positive electrode material, including improving specific capacity and cycle stability.

5. A method for preparing a nickel-manganese-based sodium ion battery positive electrode material, characterized in that: The following steps are involved: S1: Use ball milling method to mix a certain proportion of Na salt and Ni 0.25 Mn 0.75 The (OH)2 precursor is fully mixed to obtain a reaction mixture precursor; S2: calcining the reaction mixture precursor of step S1 at 400-500° C. for 5-7 hours to obtain a molten precursor; S3: heating the molten precursor to 900-1000° C. and calcining for 18-20 hours to obtain a calcined precursor of the positive electrode material; S4: naturally cooling the cathode material precursor to 400°C-600°C and maintaining the temperature for 4-5 hours to obtain the cathode material precursor; S5: Rapidly cool the cathode material precursor to room temperature using liquid nitrogen to obtain a manganese-based sodium ion battery cathode material.

6. The method for preparing the nickel-manganese-based sodium ion battery positive electrode material according to claim 5, characterized in that: Na salt and Ni 0.25 Mn 0.75 The molar ratio of (OH)2 precursor is 0.54-0.72:

1.

7. The method for preparing the nickel-manganese-based sodium ion battery positive electrode material according to claim 5, characterized in that: The Na salt is selected from the corresponding acetate or carbonate.

8. The method for preparing the nickel-manganese-based sodium ion battery positive electrode material according to claim 5, characterized in that: The cooling rate of liquid nitrogen rapid cooling is more than 10 times the natural cooling rate.

9. A nickel-manganese-based sodium ion battery positive electrode material prepared by the method as described in any one of claims 5 to 8.

10. The nickel-manganese-based sodium ion battery positive electrode material according to claim 9, characterized in that: At a voltage of 2-4.3 V, the capacity retention rate after long cycles is 80%.